Prevalence of Ectoparasites among Cattle in Kilinochchi District - Kekulandara, D.; Shathya, S.; Piratheepan, S. (University of Jaffna, 2022)
Livestock sector has been contributing considerable portion to the economy of Sri Lanka, and still promising to play great role in the economic development of the country. Products and by-products come from livestock population is an essential source of income for the people who are living in Killinochchi district. There are several constrains found in cattle farming. Among them external parasitic infestation is one of the problem which affects the production adversely. Therefore, a cross-sectional study was conducted from March to July, 2022 with the objectives of determining the prevalence of ectoparasitic infestation in cattle and risk factors associated with ectoparasitism in Kilinochchi district. Total of 384 cattle (119 males and 265 female) were used to study the prevalence on live animals. The study revealed that cattle in the study area were infested with single infestation (6.7%) and multiple infestation (45.83%) with an overall prevalence of 52.60% (202/384). Overall eight genera of ectoparasites which belong to tick (47.89%), lice (4.45%) and mite (0.26%) were identified in flank, belly, shoulder, dorsal surface of the ear and along the dorsal side of the cattle. Among the genera of the ticks, Amblyomma, Boophilus, Hyalomma, and Rhipicephalus and three types of lice genera Damalina, Linognathus and Haematopinus were found. Only one genera of mite was identified namely, Demodex bovis. According to present study, three to seven years cattle were highly susceptible (49.50%) to ectoparasitic infestation compare to other age groups. In addition, highest prevalence (70.65%) was shown by female cattle. The cattle with the herd size of less than 14 were highly infected with external parasites (79.60%). The present study revealed that widespread occurrence of ectoparasites in cattle in the study area, thus, improved management practice and well-coordinated control interventions are required.
Keywords: Cattle; Ectoparasite; Lice; Mite; Prevalence